Pengaruh Motivasi, Ekspektasi Pendapatan, dan Persepsi Mahasiswa terhadap Minat Berwirausaha dengan Pemahaman Akuntansi sebagai Variabel Moderating - Ridhia Melliyani Noor; Saiful Anwar (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
The purpose of this study was to describe the effect of motivation, income expectations, student perceptions of interest in entrepreneurship with accounting understanding as a moderating variable. This type of research uses quantitative methods. The population is Accounting Students of the